2021
DOI: 10.34133/2021/2539380
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Phenomics of Field- and Greenhouse-Grown Amaranths vs. Sensory and Species Delimits

Abstract: Consumers hesitate to purchase field-grown shoot-tops of amaranths in Sri Lanka, citing the low-cleanliness making growers focus on greenhouse farming. However, the photosynthetic and growth variations in relation to the organoleptic preference of the greenhouse-grown amaranths in comparison to field-grown counterparts have not been studied. Also, the species delimits of the amaranths in Sri Lanka have not been identified, limiting our ability to interpret species-specific production characteristics. Thus, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Height measurements were only recorded again at the stage where trees were removed from the cages in September. To evaluate photosynthesis efficiency in infested and noninfested trees, quantum yield for photosystem II photochemistry was also measured using the handheld MultispeQ device (PhotosynQ Inc., East Lansing, MI, USA) (Sooriyapathirana et al 2021). Photosynthesis measurements were taken prior to insect introduction in early June, during insect exposure in August, and after insects were removed from cages in September; at this September time point photosynthetic carbon assimilation was also quantified using a portable infrared gas analyzer (CIRAS-3; PP Systems, Amesbury, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Height measurements were only recorded again at the stage where trees were removed from the cages in September. To evaluate photosynthesis efficiency in infested and noninfested trees, quantum yield for photosystem II photochemistry was also measured using the handheld MultispeQ device (PhotosynQ Inc., East Lansing, MI, USA) (Sooriyapathirana et al 2021). Photosynthesis measurements were taken prior to insect introduction in early June, during insect exposure in August, and after insects were removed from cages in September; at this September time point photosynthetic carbon assimilation was also quantified using a portable infrared gas analyzer (CIRAS-3; PP Systems, Amesbury, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Ahmadi et al 32 stated that the amount of chlorophyll of lemongrass under fluorescent lamps and LED lamps was not different. Sooriyapathirana et al 43 . reported that the chlorophyll content, as indicated by the SPAD, was significantly higher in greenhouse grown amaranths plants compared to the field grown plants.…”
Section: Leaf Pigmentsmentioning
confidence: 99%
“…Because of the closed environment and the design, the relative humidity is higher in greenhouse conditions than in the field. On the other hand, low humidity, soil pH limitation, and other possible stresses in the field condition can decrease chlorophyll concentration in field grown plants 43 .…”
Section: Leaf Pigmentsmentioning
confidence: 99%
“…It has also been established that as leaf water potential declines, stoma closure occurs to prevent water loss via transpiration, thereby limiting atmospheric CO 2 intake and inhibiting photosynthesis (Lakso and Seeley 1978). Therefore, photosynthesis parameters with respect to gas exchange, including photosynthetic carbon assimilation (A), transpiration rate (E), stomatal conductance (g s ), intrinsic water-use efficiency (WUE) (A-to-g s ratio, indicating a trade-off between photosynthesis and transpiration), and chlorophyll fluoresce, such as quantum yield for photosystem II photochemistry (Sooriyapathirana et al 2021), are identified as standard indicators for plant physiological changes under a water deficit.…”
mentioning
confidence: 99%